UNDERSTANDING THE MEANING AND MOTIVATION OF ACADEMIC FRAUD: AN EXPLORATION ON ACCOUNTING STUDENTS - Dephiena, Sukma (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2017)
Academic fraud is considered to be small fraud and always taken for granted. However, academic fraud may also effects ethics which reflects perpetrator’s professionalism. Therefore, the purpose of this research is to depict the understanding of academic fraud and to elaborate the motivation to the perpetrators. This research uses qualitative approach by interviewing accounting student conducting academic fraud. The result of this research reveals the academic fraud conducted by the accounting student in breaking the rules, the existence of fraud culture that make student doing the academic fraud, and the ambition that motivate them to do fraud.Keyword: Academic Fraud, Student Ethics, Fraud Definition, Fraud Motivation